Sustainable Business Practices and Value Creation: Peer-reviewed | Open Access Ecotourism Operators and Small and Medium Businesses in Sandakan - Chan, Jennifer Kim Lian; Beatrice Lim Fui Yee (BP Services, 2023)
This research paper presents empirical findings on the significance of sustainable practices implemented by ecotourism operators and small and medium businesses in Sandakan, Sabah. Employing a quantitative methodology, the study emphasises the awareness of environmental, social, and economic factors, as well as the challenges associated with implementing sustainable and responsible practices. The findings indicate that effective sustainable management maximises the social and economic benefits for the local community, cultural heritage, and environment, while also minimising negative impacts. Therefore, maintaining credible, sustainable, and responsible business practices in the long-term can yield positive effects on the environment, society, and economy